Pembagian Harta Bawaan Suami di Tinjau Dari Prespektif Hukum Islam - Moh Mahdi Ali Kabakoran; Barzah Latupono; La Ode Angga (Faculty of Law Universitas Pattimura, 2023)
ABSTRACT: Inheritance law is a part of civil law and specifically a part of family law. The law of inheritance is very closely related to human life, because every human being will experience a legal event, namely death. The legal event will give rise to legal consequences regarding the continuation of the rights and obligations of a person who has died and in relation to his family or other people, who are entitled to the assets left behind. These assets are in the form of inherited assets and joint assets. The aim of the research is to find out and analyze the distribution of husbands' inherited assets after death. To find out and analyze the validity of the husband's innate assets which are controlled by the wife after the husband dies. The research method used is normative legal research. Namely legal research that examines document studies, using various secondary data such as legal theories, statutory regulations and can be in the form of opinions of legal scholars. Based on the provisions in the Compilation of Islamic Law, it has been explained that. The existence of joint property in marriage does not rule out the existence of property owned by each husband and wife. The assets of each in question are inherited assets. Inheritance is the property of each husband and wife which is obtained by each as an inheritance or gift. Then the position of the inheritance is to carry the mastery of each party of the husband and wife as long as the parties do not specify otherwise in a marriage agreement.